Rusevska, K. & M. Karadelev. (2024). Macedonian Red List of Fungi: Unveiling Potential Species. 12th International Mycological Congress (IMC12). 11-15 August 2024 Maastricht, The Netherlands. (ID 1837). - Rusevska, K. & M. Karadelev. (IMC12, 2024)
The National Red List (NRL) plays an important role in the conservation of biodiversity. Macedonia is a recognized biodiversity hotspot and is home to a rich variety of fungi. Despite sporadic efforts in the past to document fungal species, research into their diversity and distribution has intensified in recent decades with the establishment of the Macedonian Mycological Laboratory. These efforts have led to the discovery of numerous previously undocumented species of fungi. The Macedonian Red List was meticulously curated through a collaborative effort involving field research, data compilation from various sources, aligning red-listing practices with IUCN guidelines and received support from international partners. The Macedonian Red List comprises 64 fungal species, with the majority belonging to Basidiomycota. However, these are only part of the species that have been categorized, and as a result of the rich biodiversity, this list can be supplemented with potential species, such as: Aspropaxillus lepistoides (Maire) Kühner & Maire, Cotylidia diaphana (Cooke) Lentz, Hemileccinum depilatum (Redeuilh) Šutara, Hericium flagellum (Scop.) Pers, Lactarius mairei Malençon, Pachyella violaceonigra (Rehm) Pfiste, Peniophora boidinii D.A. Reid, Podofomes trogii (Fr.) Pouzar, Pogonoloma macrorhizum (Quél.) Dima & P.-A. Moreau, Phellodon connatus (Schultz) P.Karst., Scutiger pes-caprae (Pers.) Bondartsev & Singer. The NRL serves as a crucial tool for conservation efforts, providing a comprehensive understanding of the status of Macedonian mycobiota. The identification of potentially red listed species highlights the urgent need for targeted conservation strategies to mitigate threats and ensure the preservation of fungal diversity in the region.
Keywords: Potential red list species, Macedonia